The Effect of Organizational Well-Being on Organizational Commitment in Telecommunication Employees - Islaha, Shafia; Kadiyono, Anissa Lestari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
At work, an effective environment will increase a person's work productivity. Efforts to study this condition can be made by examining organizational well-being. This research was conducted to find out whether organizational well-being perceived by employees influences employee commitment to the company where they work. The population in this study was 128 telecommunication employees who were selected using stratified random sampling techniques. Data collection was carried out through an organizational well-being questionnaire developed by (I Prilleltensky, 2007) and an organizational commitment questionnaire adapted and modified from (JP Meyer, 1997) questionnaire. Hypothesis testing uses simple regression analysis techniques. The results showed that organizational well-being has a significant influence on the three components of organizational commitment, namely affective commitment, continuance commitment, and normative commitment. In this study, data was found that Organizational well-being contributes the most to affective commitment compared to other components.Dalam bekerja, lingkungan yang efektif akan meningkatkan produktivitas kerja seseorang. Upaya untuk menelaah kondisi ini dapat dilakukan dengan menelaah organizational well-being. Penelitian ini dilakukan untuk mengetahui apakah organizational wellbeing yang dipersepsi oleh karyawan berpengaruh pada komitmen karyawan terhadap perusahaan tempatnya bekerja. Populasi dalam penelitian ini adalah karyawan telekomunikasi sejumlah 128 orang yang dipilih menggunakan teknik stratified random sampling. Pengumpulan data dilakukan melalui kuesioner organizational well-being yang dikembangkan dari teori (I Prilleltensky, 2007) dan kuesioner organizational commitment yang diadaptasi dan dimodifikasi dari kuesioner (JP Meyer, 1997). Pengujian hipotesis menggunakan teknik analisis regresi sederhana. Hasil penelitian menunjukkan bahwa organizational well-being memiliki pengaruh yang signifikan terhadap ketiga komponen organizational commitment yaitu affective commitment, continuance commitment, dan normative commitment. Dalam penelitian ini, didapati data bahwa Organizational well-being berkontribusi terbesar terhadap affective commitment dibandingkan dengan komponen lainnya.